Geological and Geomorphological Evaluation of Kolleru-Upputeru catchment using Geospatial Technologies - Raghuram, P; Rambabu, T; A.R.K Raju, P; Sankara Pitchaiah, P (International Journal of Engineering and Technology, 2018)
Kolleru Lake is a unique world famous wetland ecosystem. It is one of the prime coastal ecosystems in India and regarded as Ramsar site. It is located in the coastal tracts of Krishna and West Godavari districts of Andhra Pradesh. Overexploitation and mismanagement of land and water resources are exerting detrimental impact on the lake environment. The striking manifestation of this phenomenon is seen various kinds of problems such as shrinkage in Lake area, floods in foreshore area, pollution and siltation of lake, sea water intrusion, land degradation etc. The challenge therefore is, to arrest the degradational processes and restore the lake eco-system. The generation and evaluation spatial information on the terrain conditions that include Tectonic frame work, Lithology, Structure and Geomorphology of the area using geospatial technologies carried out in  the present study forms an important component to address various issues in respect of land and water  resources. Thus, the spatial database facilitates to formulate a scientific plan for the conservation, restoration and management of Kolleru lake ecosystem.